The Decline of Mabbarazanji: Customary Religious Practice in the Lens of Islamic Legal Philosophy - Hardianti, Hardianti; Basri, Rusdaya; Badruzzaman, Badruzzaman; Ismail, Muhammad (Jurnal Marital: Kajian Hukum Keluarga Islam, 2024)
This study examines the Mabbarazanji tradition in post-wedding ceremonies within the Bugis community of Kandiawang, South Sulawesi, through the lens of Islamic legal philosophy. As a locally rooted religious practice, Mabbarazanji encapsulates collective recitations, symbolic offerings, and communal participation that transcend its ritualistic function to embody cultural identity and spiritual values. The research aims to explore how the tradition is practiced, perceived by the community, and positioned within the framework of ‘urf (custom) and maqāṣid al-sharī‘ah (objectives of Islamic law). Employing a qualitative fieldwork design, data were gathered over two months through participant observation, semi-structured interviews with religious and cultural leaders, and documentation of the ceremony. Thematic analysis revealed that Mabbarazanji is not only considered a sacred obligation but also a medium for transmitting ethical values such as unity, loyalty, and gratitude. Symbolic items—such as sticky rice, bananas, and eggs—convey culturally embedded meanings that align with Islamic virtues. The discussion situates Mabbarazanji as a case of dynamic religious embodiment, where local tradition and Islamic legal principles coexist. While generational disengagement poses challenges to its continuity, the ritual’s alignment with sharī‘ah norms and its capacity to promote social cohesion underscore its theological and cultural legitimacy. This study contributes to the discourse on the integration of local customs within Islamic jurisprudence and highlights the role of vernacular ritual in preserving ethical traditions in the face of modern transformation.